1999
DOI: 10.1002/(sici)1097-4644(19990915)74:4<587::aid-jcb8>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

1,25 dihydroxyvitamin D3 and dexamethasone induce the cyclooxygenase 1 gene in osteoclast-supporting stromal cells

Abstract: Commitment of members of the monocyte/macrophage family to the bone resorptive phenotype, in vitro, requires contact, of these osteoclast precursors, with osteoblasts or related stromal cells. The osteoclast-inductive properties of these stromal cells are typically expressed, however, only in the presence of steroid hormones such as 1,25 dihydroxyvitamin D (1,25D3) and dexamethasone (DEX). To gain insight into the means by which steroid treated accessory cells induce osteoclast differentiation we asked, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…It was also shown to be up-regulated in a hormone-treated, osteoclastogenic mouse bone marrow stromal cell line ST2 (35). Indeed, we found that conditioned medium from the ST2 cell line treated with 1,25-dihydroxyvitamin D 3 and dexamethasone was chemotactic for CMKLR1 transfectants (data not shown).…”
Section: Discussionmentioning
confidence: 71%
“…It was also shown to be up-regulated in a hormone-treated, osteoclastogenic mouse bone marrow stromal cell line ST2 (35). Indeed, we found that conditioned medium from the ST2 cell line treated with 1,25-dihydroxyvitamin D 3 and dexamethasone was chemotactic for CMKLR1 transfectants (data not shown).…”
Section: Discussionmentioning
confidence: 71%
“…Dexamethasone in combination with 1,25 dihydroxivitamin D3 induces chemerin in osteoclast-supporting stromal cells [38] but the effects of steroids alone on chemerin expression have not been analysed in detail so far.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that PAR-2 caused a suppression of expression of the supposedly constitutive PGHS-1 in 3-day bone marrow cultures was not entirely surprising, because this enzyme has previously been found to be regulated in ST2 stromal cells. (37) What is the physiological significance of our observation that PAR-2 activation results in inhibition of PTH-and 1,25(OH) 2 D 3 -induced osteoclast differentiation? The PAR-2-null mice used in this study had grossly normal skeletons, (27) and PAR-2-null mice from other groups are also described as being grossly normal, (38,39) although no detailed study of bone development and structure has yet been carried out.…”
Section: Smith Et Almentioning
confidence: 99%